A physical alpha-power law MOSFET model - Bowman, K.A.; Austin, B.L.; Eble, J.C.; Xinghai Tang; Meindl, J.D. (IEEE journal of solid-state circuits, 1999)
A new compact physics-based alpha-power law MOSFET model is introduced to enable projections of low power circuit performance for future generations of technology by linking the simple mathematical expressions of the original alpha-power law model with their physical origins. The new model, verified by HSPICE simulations and measured data, includes: 1) a subthreshold region of operation for evaluating the on/off current tradeoff that becomes a dominant low power design issue as technology scales, 2) the effects of vertical and lateral high field mobility degradation and velocity saturation, and 3) threshold voltage roll-off. Model projections for MOSFET CV/I indicate a 2X-performance opportunity compared to the National Technology Roadmap for Semiconductors (NTRS) extrapolations for the 250, 180, and 150 nm generations subject to maximum leakage current estimates of the roadmap. NTRS and model calculations converge at the 70 nm technology generation, which exhibits pronounced on/off current interdependence for low power gigascale integration.